A forest of guesswork ... or the intricacies of social interaction between children in kindergarten around the picture books - Manuela Ferreira; Cristina Madureira (Universidade Federal de Santa Catarina, 2014)
Based on an interactive episode taken from the field notes of fieldwork with a group of 10 children between 5 and 6 years old , in the context of kindergarten ( JI ) , this article mobilizes contributions Sociology of Childhood to account for the social uses children make picture books when used on its own initiative, and the ways in which i) demonstrate your agency in the construction of social identity in the group and ii ) their meaning symbolically illustrated books , objects of cultural production for adult children; iii) are used strategically and symbolic power relations and sociability that is playing in her womb. To redefine the picture book as an object for use by children, we aim to contribute to the awareness of the need to i) reassess the role of the book in time and space of everyday JI ii) reassess the practice of using illustrated book with children in institutional context; iii) reconfigure the book as a cultural object producer intersubjective meanings iv) reconfigure the illustrated book as an object of social transactions and cultural appropriation by children who use it, the peer group, and finally v) review the conceptions of childhood that underpin the choice and selection of printed materials that are available for children's use.